The oncogenic role of human papillomavirus in breast cancer: a comprehensive systematic review and meta-analysis - Koishybayeva, Dana; Balmagambetova, Saule; Zhakiev, Bazylbek; Koishybayev, Arip; Mussin, Nadiar M.; Sakhanova, Svetlana; Aitmagambetova, Marzhan; Tulyayeva, Anar; Tamadon, Amin (Frontiers in Microbiology, 2025)
IntroductionHuman papillomavirus (HPV) has been increasingly implicated in the pathogenesis of breast cancer (BC), though its role remains controversial. Understanding HPV prevalence and genotype distribution across histological types and regions may clarify this potential association.MethodsA comprehensive systematic review and meta-analysis was conducted using PubMed, Scopus, and Web of Science databases for studies published between January 1990 and April 2025. Eligible studies reported HPV prevalence in BC tissues stratified by histological classification. Non-English studies, reviews, and those lacking histological stratification were excluded. Data from 49 studies encompassing 4,173 BC cases were extracted. Pooled HPV prevalence and odds ratios (ORs) were calculated using random-effects models. Subgroup analyses were performed by histology, geographic region, and HPV genotype (16/18). Risk of bias was assessed using the Joanna Briggs Institute (JBI) checklist for cross-sectional studies and the Newcastle–Ottawa Scale for case-control designs.ResultsThe pooled prevalence of HPV in BC tissues was 23% (95% CI: 18–28%), highest in invasive ductal carcinoma (24%). HPV-positive individuals exhibited a 3.6-fold higher risk of developing BC (OR = 3.63, 95% CI: 2.33–5.64), with the strongest association in invasive lobular carcinoma (OR = 4.41). HPV-18 showed a more consistent correlation with BC than HPV-16. Regional variation was observed, with Asian populations showing higher HPV prevalence and stronger associations.DiscussionThis meta-analysis suggests a significant association between HPV infection—particularly genotype 18—and breast cancer risk, especially in Asian regions and specific histological subtypes. These findings highlight the need for mechanistic studies and standardized molecular detection to elucidate the potential oncogenic role of HPV in breast tissue.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/display_record.php?RecordID=1051960 identifier CRD420251051960